Pengaruh Likuiditas, Profitabilitas dan Debt to Equity Ratio terhadap Harga Saham Perusahaan SubSektor Pertambangan Batubara yang Terdaftar di BEI Tahun 2022-2023 - Jein, Khomarudin; Febriansyah Putra, Farhan; Puspita Ayu, Mayang; Syifa Khaerunisa, Dhea; Agung Pambudi, Aditya; Nyoman Sawitri, Ni (Fibonacci: Jurnal Ilmu Ekonomi, Manajemen dan Keuangan, 2024)
This research aims to analyze the effect of liquidity, profitability, and the debt to equity ratio (DER) on stock prices of coal mining sub-sector companies listed on the Indonesia Stock Exchange (IDX) during 2022-2023. The method used is a comparative analysis of journal reviews. The results of this research can potentially serve as a reference for researchers and academics interested in the field of corporate financial analysis and financial management, with data derived from financial statements and stock market data of the companies. The findings indicate that liquidity has a significant positive effect on stock prices, suggesting that companies with higher liquidity tend to have better stock prices. Additionally, profitability also has a positive impact, reflecting the importance of profit performance in determining stock value. On the other hand, the debt to equity ratio (DER) shows a negative effect on stock prices, indicating that higher debt levels may reduce investor confidence. These findings provide insights for investors and company management in making decisions related to investment and financial strategies in the coal mining sector.